Effects of Moral Self, Self Esteem and Parental Bonding on Delinquency among Young People in Hong Kong - Cheng, Po F.; Cheng, Christopher H.K. (International Journal of Criminology and Sociology, 2015)
This study was designed to investigate the effects of global self-esteem, moral self, and parental bonding on youth’s delinquency. A sample of young Chinese adults (N=200) were drawn from public areas such as playgrounds and campus. Respondents were to complete a questionnaire consisted of the General Self, Moral Self, Parental Bonding, and Behavior Checklist on an individual basis. As a result, males reported higher delinquency as well as general self-esteem than females. Among the demographic variables, gender was found to significantly predict delinquency. For the self variables, moral self but not global self-esteem was found to predict delinquency significantly, even when the effect of gender was being controlled. Among the parenting aspects (authoritarianism, protectiveness, care), protectionism significantly predicted delinquency, while parental care and authoritarianism did not. These findings confirmed the need of considering multidimensional aspects of self-esteem and the cultural perspective in explaining the parental impacts on delinquency.